Dealing with farming system diversity in northern Ghana: Typology approaches - Kuivanen, K.S. (Wageningen University & Research, 2015)
Typologies may be used as tools for dealing with farming system heterogeneity. This is achieved by classifying farms into groups that have common characteristics, i.e. farm types, which can support the implementation of a more tailored approach to agricultural development. This article explored patterns of farming system diversity in Ghana’s Northern Region through the classification of 80 smallholder farm households. Based on 2013 survey data, the typology was constructed using the multivariate statistical techniques of principal component analysis and cluster analysis. Results proposed six farm types, stratified on the basis of household, labour, land use, livestock and income variables, explaining the structural and functional differences between farming systems. Types 1 and 2 were characterized by relatively high levels of resource endowment and oriented towards non-farm activities and crop sales respectively. Types 3 and 4 were moderately resource endowed with income derived primarily from on-farm activities. Types 5 and 6 were resource constrained, with production oriented towards subsistence. It was found that livelihood strategies reflect the distinctive characteristics, opportunities and constraints of farm households- with poorly endowed types restricted to a ‘survival strategy’ and more affluent types free to pursue a ‘development strategy’. We conclude that a more flexible approach to typology construction, for example through the incorporation of farmer perspectives, might provide further context and insight into the drivers of diversity.